2021
DOI: 10.3390/en14144126
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Carbon Disclosure on Financial Performance under Low Carbon Constraints

Abstract: In the context of low-carbon constrained development, in order to avoid the risk brought by climate change, more and more companies choose to disclose carbon information, respond to the national policy of carbon emission reduction and focus on the sustainable development of enterprises. This paper will investigate the impact of carbon disclosure on financial performance based on the 2011–2018 CDP report, taking the Fortune 500 companies as a sample. The study finds that for carbon-intensive industries, carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 51 publications
3
18
0
2
Order By: Relevance
“…The results show that carbon performance can positively affect financial performance, which means that the better of carbon performance will promote the better of financial performance. This outcome of the study is in line with the prior work of He et al (2017) , Gaigné et al (2020) , Zhu and Zhang (2022) , Lu et al (2021) , Li and Lin (2021) , Yuan and Guangpei (2021) , and technological innovation can also positively affect financial performance significantly. In other words, both carbon performance and technological innovation are driving factors of corporate financial performance.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results show that carbon performance can positively affect financial performance, which means that the better of carbon performance will promote the better of financial performance. This outcome of the study is in line with the prior work of He et al (2017) , Gaigné et al (2020) , Zhu and Zhang (2022) , Lu et al (2021) , Li and Lin (2021) , Yuan and Guangpei (2021) , and technological innovation can also positively affect financial performance significantly. In other words, both carbon performance and technological innovation are driving factors of corporate financial performance.…”
Section: Discussionsupporting
confidence: 87%
“…The reduction of carbon emissions leads to the reduction of energy consumption ( He et al, 2017 ), especially for energy companies, which can continue the capture of corporate value. Lu et al (2021) found that the positive impact of carbon disclosure on financial performance can be extended to the next period. Therefore, formulating active and effective carbon strategies can not only adapt to today’s development trends, but also meet the needs of stakeholders.…”
Section: Related Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Scaling down the big picture at the level of businesses, more and more companies choose to disclose carbon information, respond to the national policy of carbon emis-sion reduction and focus on the sustainable development of enterprises. The paper of Lu et al [6] investigates the impact of carbon disclosure on financial performance based on the 2011-2018 CDP report, taking the Fortune 500 companies as a sample. The study finds that for carbon-intensive industries, carbon disclosure cannot significantly contribute to the improvement of financial performance in the current period, but for carbon-non-intensive industries, carbon disclosure can significantly contribute to the improvement of financial performance in the current period, and the positive impact of carbon disclosure on financial performance in the current period can be extended to the next period.…”
Section: Scientific Contribution Of This Special Issue: a Brief Overviewmentioning
confidence: 99%
“…Companies gain more than they might anticipate from carbon information measurement and publication [ 18 ]. For instance, effective carbon disclosure can assist businesses in managing their financial risk [ 19 ]. Carbon disclosure will considerably lower the cost of corporate borrowing for companies with subpar carbon performance [ 20 ].…”
Section: Introductionmentioning
confidence: 99%